2019
DOI: 10.1111/head.13536
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, Birth, Neonatal, and Postnatal Neurological Outcomes After Pregnancy With Migraine

Abstract: Background Prevalence of migraine is high during the reproductive age. Although migraine often improves during pregnancy, the risk of adverse pregnancy, birth, neonatal, and neurological outcomes in mother and offspring remains poorly understood. Objective To investigate the associations between maternal migraine and risks of adverse pregnancy outcomes in the mother, and birth, neonatal and postnatal outcomes in the offspring. Methods We used Danish population registries to assemble a cohort of pregnancies amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 36 publications
(119 reference statements)
4
55
1
3
Order By: Relevance
“…As expected, use of medications before and during pregnancy was considerably higher in our migraine study sample than the general population of pregnant women. During the first trimester, preventive medication use ranged from 10–16%; other studies in similar populations not limited to specific diagnoses noted much lower prevalence (2224), as did a study among pregnant women with migraine (25). However, the overall pattern of pharmacotherapy discontinuation in our study, with greater discontinuation for preventive drugs and less for acute treatments other than triptans, is consistent with many drug utilization studies in pregnancy in both the US (26,27) and Europe (28).…”
Section: Discussionmentioning
confidence: 70%
“…As expected, use of medications before and during pregnancy was considerably higher in our migraine study sample than the general population of pregnant women. During the first trimester, preventive medication use ranged from 10–16%; other studies in similar populations not limited to specific diagnoses noted much lower prevalence (2224), as did a study among pregnant women with migraine (25). However, the overall pattern of pharmacotherapy discontinuation in our study, with greater discontinuation for preventive drugs and less for acute treatments other than triptans, is consistent with many drug utilization studies in pregnancy in both the US (26,27) and Europe (28).…”
Section: Discussionmentioning
confidence: 70%
“…24 Offspring prenatally exposed to maternal migraine had elevated risks of intensive care unit admission, dispensed prescriptions, respiratory distress syndrome, and febrile seizures. 23,25 Most of the adjusted risk ratios for adverse fetal outcomes were less than 1.5.…”
Section: Discussionmentioning
confidence: 98%
“…4,21,22 However, some studies have reported that active migraine is a modest risk factor for poor pregnancy outcomes, such as gestational hypertension, preeclampsia, ischemic stroke, myocardial infarction, deep vein thrombosis, pulmonary embolus, miscarriage, increased prevalence of low birth weight, preterm birth, and cesarean delivery. 23 More severe forms of migraine with frequent attacks during pregnancy may be associated with poorer outcomes. 24 Offspring prenatally exposed to maternal migraine had elevated risks of intensive care unit admission, dispensed prescriptions, respiratory distress syndrome, and febrile seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified associations between migraine and pre-eclampsia or gestational hypertension 36 37. There is some evidence to suggest an increased risk in women with preterm births (OR 1.24) and low birth weight (OR 2.74) 38 39…”
Section: Pregnancymentioning
confidence: 99%